Falling Forward: Tracing Technological Solutions for Fall Prevention in Older Adults (1996-2024) - Azizan, Azliyana; Sirada, Andy; Samosir, Nova Relida (Information Research Communications, 2024)
This bibliometric analysis investigates technological solutions for fall prevention in older adults by examining 105 articles from 1996-2024 in the Web of Science database. Utilizing advanced techniques, it maps publication trends, contributors, research hotspots, themes, influential works and emerging topics. Findings reveal increasing research output after 2012, led by the U.S., U.K. and Australia. Prominent hotspots include virtual reality, digital health tools and multidisciplinary interventions. Highly cited works highlight virtual reality, wearable devices and fall prevention education. Emerging areas focus on virtual reality, wearable technologies, mHealth solutions and gait biomarkers. These findings inform geriatric fall prevention research and clinical translation.
Keywords: Bibliometric; Fall; Older Adults; Technology